Increased Expression of Zyxin and Its Potential Function in Androgenetic Alopecia - Qingmei Liu; Xiangguang Shi; Yue Zhang; Yan Huang; Kai Yang; Yulong Tang; Yanyun Ma; Yuting Zhang; Ji'an Wang; Li Zhang; Qi Zhang; Xiao Liu; et al. (Frontiers in Cell and Developmental Biology, 2021)
Androgenetic alopecia (AGA) is the most common progressive form of hair loss, occurring in more than half of men aged > 50 years. Hair follicle (HF) miniaturization is a feature of AGA, and dermal papillae (DP) play key roles in hair growth and regeneration by regulating follicular cell activity. Previous studies have revealed that adhesion signals are important factors in AGA development. Zyxin (ZYX) is an actin-interacting protein that is essential for cell adhesion and migration. The aim of this research was to investigate the expression and potential role of ZYX in AGA. Real-time polymerase chain reaction (RT-PCR) analysis revealed that ZYX expression was elevated in the affected frontal HF of individuals with AGA compared to unaffected occipital HF. Moreover, increased ZYX expression was also observed within DP using immunofluorescence staining. Our in vivo results revealed that ZYX knockout mice showed enhanced hair growth and anagen entry compared to wild-type mice. Reducing ZYX expression in ex vivo cultured HFs by siRNA resulted in the enhanced hair shaft production, delayed hair follicle catagen entry, increased the proliferation of dermal papilla cells (DPCs), and upregulated expression of stem cell-related proteins. These results were further validated in cultured DPCs in vitro. To further reveal the mechanism by which ZYX contributes to AGA, RNA-seq analysis was conducted to identify gene signatures upon ZYX siRNA treatment in cultured hair follicles. Multiple pathways, including focal adhesion and HIF-1 signaling pathways, were found to be involved. Collectively, we discovered the elevated expression of ZYX in the affected frontal hair follicles of AGA patients and revealed the effects of ZYX downregulation on in vivo mice, ex vivo hair follicles, and in vitro DPC. These findings suggest that ZYX plays important roles in the pathogenesis of AGA and stem cell properties of DPC and may potentially be used as a therapeutic target in AGA.